2018
DOI: 10.1002/erv.2633
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of specific psychopathology and psychiatric symptoms in patients with anorexia nervosa

Abstract: In addition to ED-core symptoms, psychiatric comorbid symptoms should be the focus of specific treatments in patients with AN, independently from BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
66
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 44 publications
(64 reference statements)
15
66
0
Order By: Relevance
“…The present findings are in line with previous studies which identified anxiety and depressive symptoms as well as interpersonal difficulties and ineffectiveness as the most central nodes in adult outpatients with mixed ED diagnoses (Solmi et al, ) and in an adult outpatient AN sample (Solmi et al, ). Another recent work also proved that negative affect symptoms, such as low self‐esteem, concentration difficulties, feeling overwhelmed and nervousness as well as shape and weight related concerns are central nodes in a network comprising a hospitalized adult ED population before and after treatment (Smith et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The present findings are in line with previous studies which identified anxiety and depressive symptoms as well as interpersonal difficulties and ineffectiveness as the most central nodes in adult outpatients with mixed ED diagnoses (Solmi et al, ) and in an adult outpatient AN sample (Solmi et al, ). Another recent work also proved that negative affect symptoms, such as low self‐esteem, concentration difficulties, feeling overwhelmed and nervousness as well as shape and weight related concerns are central nodes in a network comprising a hospitalized adult ED population before and after treatment (Smith et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our hypothesis, we detected some differences in our NA of adolescents with AN at the early stage of the illness compared to the findings of studies on adult AN patients (Solmi et al, ). In particular, asceticism and anxious physical symptoms seem to play a pivotal role in adolescents with AN.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations